شیخ عبدالحق محدث دہلوی کی علمی خدمات، منہج واسلوب اورعوامی مقبولیت و اثرات؛ ایک تحقیقی جائزہ : A Research Review of the Work of Sheikh Abdul Haq Muḥaddith Dehlavi, It’s Style, Public Populaity & Influence - Turabi, Fazal Haq Turabi; Ahmad, Dr. Sheraz (Al-Amīr Research Journal for Islamic Studies, 2023)
Sheikh Abdul Haq Muḥaddith Dehlavi is one of the prominent muhaddithin of the Subcontinent. He has played an unforgettable role in the leadership of the Ummah. His writings consist of God’s benevolence, justice, and solving People’s problems so that they can look at their defects and focus on building their lives. He discussed topics related to the nation; do not follow useless philosophy and false interpretations which do not benefit a common man. Along with the reformed works, He has also left behind a large collection on technical topics. He wrote books on important and technical topics such as Tafseer, Tajweed, Hadith, Beliefs, Jurisprudence, Sufism, Ethics, Actions, Philosophy, History, Biography, etc. Sheikh Abdul Haq Muhaddith Dehlavi has priority in teaching and publishing the knowledge of Hadith. In the context of the publication of the knowledge of hadith, his two commentaries Mishkwat al-Masabih, Ishaat al-Lamaat and Lamaat al-Tanqeeh, has a special place. In the said article, an introduction and methodological study of the work done by Sheikh Abdul Haq will be presented.